EFFICIENT TECHNIQUE FOR AUTOMATIC EXTRACTION AND IDENTIFICATION OF ELEVATION FROM A REFERENCE IMAGE - Pradhan, Mohan Pratap; Ghose, Mrinal Kanti; Mittal, Gourav (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In Geographic information system (GIS) identification of elevation detail pertaining to a contour in a reference map or topological map plays an important role while creating digital elevation model or digital surface model of a terrain. Traditional technique involving manual identification of elevation demands greater effort and time where in one needs to tediously identify and enter the elevation value. These identified elevations can be later used for creating digital elevation model. In order to reduce the complexity involved in same, effective and efficient automated technique can be devised that identifies the elevation associated with a contour. In addition the automated technique should also ensure correctness and reliability of the elevation details identified. The alignment of elevation details in the feature space adds to the complexity of the problem. Over years several techniques have been proposed based on object oriented technique and pattern detection. Â This proposed work introduces a novel rotation invariant technique for identifying number associated with contours taking into consideration friend pattern chain of the significant pixels representing a digit in a number.